The accurate shape of salt diapir and near-salt commercial hydrocarbon pools: outcome of applying a 3D joint gravity, well-log, seismic inversion, and new paradigm for pool mapping - О.П. Петровський; Т.О. Петровська; О.М. Оніщук; В.М. Суятинов; П.М. Чепіль (Геофизический журнал, 2025)
Limitations of the seismic method in mapping salt diapirs increase exploration risks while drilling in near-salt areas. An innovative method of 3D joint inverse problem solution for gravity, well-log, and seismic data makes it possible to verify and refine the shape of a salt dome and map hydrocarbon accumulations right beside the salt wall under the salt wing and over the salt dome. It is illustrated by the results for four salt domes in the central axial part of the Dniper-Donets Basin. In half of the cases, joint gravity inversion proved that seismic data provided a reliable salt shape that may be used as the biggest outline. In the other half of the cases, the salt stem outlined by 3D gravity inversion significantly differed from that by 2D and 3D seismic data interpretation. In one case, gravity inversion showed that the size of the salt stem was three times smaller. For all the cases under the salt wing in proximity to the salt dome, near the salt wall, and over the salt dome, localized low-density rock areas were mapped. These areas were associated with commercial hydrocarbon pools. For one, the salt dome location of the commercial pools was verified by drilling. As a result, a new oil field was discovered and named after Academician Schpak. Also, over the same salt dome, the size of the Runovshina field shallow gas pool outline was six times expanded. Four wells drilling outcomes ― three commercial and one dry ― fully confirm the correctness of the shape of the mapped commercial pool with a 100 % commercial probability of success.